Hearts and bones [videorecording (DVD)] - Lawrence, Ben, 1973-; Weaving, Hugo, 1960-; Luri, Andrew; McElhinney, Hayley, 1974-; Watson, Bolude (Gravitas Ventures, 2020)
"Dan, a renowned war photographer struggling with PTSD, forms an unexpected bond with Sebastian, a Sudanese refugee, until one of his photographs unearths a dark secret from Sebastian's past"--back cover.